Land-based salmon farming : an assessment of the nearshoring potential of emerging countries in Europe - Brevik, Roy Schjølberg (2019)
Atlantic salmon is the highest valued species in the European aquaculture sector with a production value of almost four billion euros in 2014. The species requires a special farming environment for optimal growth and only a few countries have the right water conditions to farm salmon in the ocean. One of them is Norway, who over the last years has experienced problems with sea lice and escapes of salmon in the traditional “open sea cage” farming method. Thus, several players have started to investigate the opportunities for relocating salmon farming to cages on land. Hence, the objective of this study is to analyze what emerging country in Europe that is most optimal for Norwegian salmon farmers to nearshore land-based salmon farming. Emerging countries in Europe are usually attractive for nearshoring because of geographical proximity, low labor costs and access to highly talented-and skilled labor. The study was supported by secondary research and interviews with industry experts where the MCDM technique SMART were used to evaluate all the emerging countries based on the findings. According to the SMART analysis, Russia is the most optimal country for nearshoring land-based salmon farming, a country that is currently experiencing a boom in the domestic aquaculture sector after the ban on import of seafood in 2014. O salmão do Atlântico é a espécie de maior valor no setor aquícola europeu, com um valor de produção de quase quatro bilhões de euros em 2014. A espécie requer um ambiente agrícola especial para um crescimento ótimo e apenas alguns países têm condições de água corretas para cultivar salmão no oceano . Uma delas é a Noruega, que nos últimos anos experimentou problemas com piolhos do mar e escapes de salmão no tradicional método de cultivo "gaiola em mar aberto". Assim, vários atores começaram a investigar as oportunidades de realocar a criação de salmão para gaiolas em terra. Assim, o objetivo deste estudo é analisar qual é o país emergente na Europa que é melhor para os produtores de salmão noruegueses para o cultivo de salmão em terra. Os países emergentes na Europa são geralmente atraentes para o nearshoring devido à proximidade geográfica, baixos custos de mão-de-obra e acesso a mão-de-obra altamente qualificada e qualificada. O estudo foi apoiado por pesquisas secundárias e entrevistas com especialistas do setor, onde a técnica MCDM SMART foi usada para avaliar todos os países emergentes com base nos resultados. De acordo com a análise da SMART, a Rússia é o país mais ideal para o nearshoring de cultivo de salmão em terra, um país que está experimentando atualmente um boom no setor de aqüicultura doméstica após a proibição de importação de frutos do mar em 2014.